Bank Loans Types and Economic Growth - Literature Review - Thaçi, Lumnije (European Journal of Economics and Business Studies, 2022)
For the economic and financial stability of a country, the banking sector also has a very important role. The importance of this sector in maintaining stability was further confirmed during the presentation of the global financial and economic crisis of 2007, wherein the following years greater attention was paid to it in terms of the regulation (Basel III) of operation of the banking sector in order to avoid financial crises. With the evolution of human society, with the evolution of money forms and the growth of international trade transactions, the development of the financial system took on an ever-increasing role in the growth and development of the economy. Considering this, the aim of this paper is to review and analyse the theoretical and empirical work related to the impact of bank loans on economic growth. According to the theoretical literature, the development of the financial system accelerates economic growth. In this study, the empirical work related to the impact of short-term and long-term loans on the economy, the impact of loans in a particular sector of the economy, but also the impact of aggregate loans on the economy was reviewed. For the effect of loans on the economy to be greater, credit placement must be oriented towards productive projects. Also of particular importance is policy reform in this sector.
Keywords: Banking system, economic growth, bank loans, types of loans